From theory to action : women, gender, and development - Wickramasinghe, Maithree; Friedrich-Ebert-Stiftung (Sri Lanka) (Colombo : Friedrich-Ebert Stiftung, 2000)
Critical analyses of the theoretical concepts of women in development, and gender and development; also examines the application of these approaches in programs of non governmental organisations in Sri Lanka.
Keywords: Women in development -- Sri Lanka; Social participation -- Sri Lanka